The Perspectives of Legal Progressivism Concerning Song Royalty Payments - Dina Kurniawati (Syiah Kuala Law Journal, 2022)
The Royalty is actually an economic right that must be accepted by the creator as a form of respect and reward for a work. In this case, the existence of rules regarding the payment of royalties is important in ensuring legal certainty. Even so, the economic right to pay royalties must also take into account social realities. This is especially the case when cafés are subject to royalty payments for music and songs. Of course, the lack of clarity about the meaning of café makes every coffee shop also have to pay royalties. This research is a normative legal research with legal issues of legal ambiguity on the meaning of café. This research is a juridical-normative research. The research uses two approaches, namely the legislation approach and the concept approach. The legal materials in this study are primary legal materials which include: the 1945 Constitution of the Republic of Indonesia, Law no. 28 of 2014 concerning Copyright, and Government Regulation No. 56 of 2021 concerning Management of Song and/or Music Copyright Royalties. Secondary legal materials include: books, journal articles, to research results. Non-legal materials include language dictionaries. The results of the study confirm that the progressive legal aspect of royalty payments must place royalties not only as a right but also as an effort to promote public welfare. The emphasis on the creator's economic rights in paying royalties is actually contrary to the value of justice from a progressive legal perspective. Thus, the President should revise the PP royalty by providing firm, clear, and limitative information.